Designing A Website Application For Diagnosing Respiratory Tract Diseases Using Forward Chaining Method And Certainty Factor - Iqbal Maulana Akbar; Devi Yunita; Maulana Fansyuri (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
An expert system is a computer-based system that uses knowledge, facts, and reasoning techniques to solve problems that normally can only be solved by an expert in a particular field. Expert systems provide added value in technology to assist in the face of an increasingly sophisticated information age. This Expert System application is based on a website built using the PHP programming language and MySQL database (PhpMyAdmin). This expert system application also produces output in the form of possible respiratory tract diseases suffered by the symptoms felt by the user. The system uses the forward chaining method and uses the certainty factor method to obtain confidence in the percentage of the disease suffered by the user. Keywords : Respiratory tract diseases, Expert System, Forward Chaining, Certainty Factor